Cambiarenes: Single‐Step Synthesis and Selective Zwitterion Binding of a Clip‐Shaped Macrocycle with a Redox‐Active Core. Issue 9 (30th January 2020) - Petersen, Riley J.; Rozeboom, Brett J.; Oburn, Shalisa M.; Blythe, Nolan J.; Rathje, Tanner L.; Luna, Javier A.; Kibby, Steven K.; O'Brien, Emily A.; Rohr, Kayleigh G.; Carpenter, Joshua R.; Sanders, Taylor L.; Johnson, Andrew M.; et al.
Abstract: A novel macrocyclic host molecule was synthesized that forms in a single step from commercially available starting materials. The core of the macrocycle backbone possesses two quinone rings and, thus, it is redox‐active. Host–guest binding involving the clip‐shaped cavity indicates selective binding of pyridine N ‐oxides based on the electron density of and steric bulk around the anionic oxygen. Abstract : A novel macrocyclic host molecule has been synthesized that forms in a single step from commercially available starting materials. The core of the macrocycle backbone possesses two quinone rings and, thus, it is redox‐active. Host–guest binding involving the clip‐shaped cavity indicates selective binding of pyridine N ‐oxides based on the electron density of and steric bulk around the anionic oxygen.